Factor affecting Use Main Water Source for Households in Kendari City - Devi Savitri Effendy; Tina Searya Astuti; Astrid Pratiwi Lahata; Wiwid Arsanda (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: One of the most essential resources required by humans for sustaining life is the availability of clean water. The sources of water used by communities vary significantly, influenced by geographical conditions and socioeconomic factors. Objective: The objective of this study is to analyze the factors that influence the selection of primary water sources among households in Kendari City. Method: A descriptive method was employed to present the distribution of safe drinking water usage based on specific categories. Data were collected from the official website of the Kendari City Central Statistics Agency for the year 2020. Results: The majority (56.84%) of households in Kendari City use drilled or pumped wells as their primary water source. This is followed by 23.65% of households using protected wells or springs. Households using drilled or pumped wells are generally characterized by household heads with at least a junior high school education and medium-level expenditures. In contrast, households using protected wells or springs typically have household heads with primary education or below, and lower levels of expenditure. Conclusion: Most households in Kendari City rely on drilled or pumped wells as their main water source for daily needs such as washing, bathing, and other domestic uses. The choice of water source is closely associated with various household characteristics, particularly the education level of the household head and the household’s expenditure level. Keywords: Water, Water Source, Kendari City, Household